PENAFSIRAN BĀTHINĪ (ESOTERIS) THABĀTHABĀ’Ī DALAM TAFSĪR AL-MĪZĀN - Kerwanto (Tanzil: Jurnal Studi Al-Quran, 2016)
This paper is a review to Rosihon Anwar’s book titled “Menelusuri Ruang Batin alQur’an: Belajar Tafsir Batini pada ‘Allāmah Thabāthabā’ī”. It tries to give a picture of two important themes in this book. The first is about the nature of esoteric interpretations in the view of Thabāthabā’ī. The second is Thabāthabā’ī’s position toward hadīth that come from Shia Imams in his esoteric interpretations. The study is also to give a critical analysis to Rosihon’s idea on: (1). The periodization birth of Shia esoteric interpretations; (2). Equating of the models of Thabāthabā’ī’s esoteric interpretations with Sufi’s; (3). Thabāthabā’ī’s position toward hadīth be based from Shia Imams; and (4). Claims that, Thabāthabā’ī’s esoteric interpretations violate the context of the word.